Application of cone-beam computed tomography in the diagnostics of maxillary sinusitis of odontogenic origin – two case reports - Dobroś, Katarzyna; Zarzecka, Joanna (Journal of Stomatology, 2017)
The aim of the article is to highlight the potential for early diagnosis of maxillary sinusitis of an odontogenic origin with cone-beam computed tomography (CBCT). Two cases of long-term patients treated for maxillary sinusitis of an odontogenic origin are addressed. Dental examination combined with CBCT facilitated correct diagnosis, thus aiding optimal causal treatment. Dental treatment proved a sufficiently effective remedy in one case, whereas the other one required surgical intervention. In the case of suspected maxillary sinusitis of an odontogenic origin, close cooperation of the dentist with an otolaryngologist is recommended at an early stage of treatment. The CBCT facilitates identification of the odontogenic cause of the infection. This imaging technique allows for a simultaneous and accurate assessment of the maxillary sinuses, the teeth, and periapical tissues, whilst eliminating the need for computed tomography of the sinuses and the orthopantomograms.